2023
DOI: 10.1002/cm.21754
|View full text |Cite
|
Sign up to set email alerts
|

miR96‐ and miR182‐driven regulation of cytoskeleton results in inhibition of glioblastoma motility

Abstract: Glioblastoma multiforme (GBM) is one of the most common forms of brain tumor. As an excessively invasive tumor type, GBM cannot be fully cured due to its invasion ability into healthy brain tissues. Therefore, molecular mechanisms behind GBM migration and invasion need to be deeply investigated for the development of effective GBM treatments. Cellular motility and invasion are strictly associated with the cytoskeleton, especially with actins and tubulins. Palladin, an actin‐binding protein, tightly bundles act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
3
1
0
Order By: Relevance
“…Here, our RNA-seq analysis following LINC03045 KD revealed that WASF3 is a gene that was reproducibly downregulated with LINC03045 knockdown, while a correlation analysis of patient TCGA/GTEx sequencing data revealed a significant positive correlation between LINC03045 and WASF3. Additionally, the GO term for cytoskeleton organization (GO: 0007010) process was enriched for WASF3, which is consistent with prior literature that describes cytoskeletal reorganization as commonly associated with tumor invasion [46]. WASF3, a Wiskott-Aldrich syndrome protein family member, has been implicated in multiple studies as a regulator of the actin cytoskeleton and in cancer invasion, which is again consistent with our results [47].…”
Section: Plos Geneticssupporting
confidence: 92%
“…Here, our RNA-seq analysis following LINC03045 KD revealed that WASF3 is a gene that was reproducibly downregulated with LINC03045 knockdown, while a correlation analysis of patient TCGA/GTEx sequencing data revealed a significant positive correlation between LINC03045 and WASF3. Additionally, the GO term for cytoskeleton organization (GO: 0007010) process was enriched for WASF3, which is consistent with prior literature that describes cytoskeletal reorganization as commonly associated with tumor invasion [46]. WASF3, a Wiskott-Aldrich syndrome protein family member, has been implicated in multiple studies as a regulator of the actin cytoskeleton and in cancer invasion, which is again consistent with our results [47].…”
Section: Plos Geneticssupporting
confidence: 92%
“…Here, our RNA-seq analysis following LINC03045 KD revealed that WASF3 is a gene that was reproducibly downregulated with LINC03045 knockdown, while a correlation analysis of patient TCGA/GTEx sequencing data revealed a significant positive correlation between LINC03045 and WASF3. Additionally, the GO term for cytoskeleton organization (GO: 0007010) process was enriched for WASF3, which is consistent with prior literature that describes cytoskeletal reorganization as commonly associated with tumor invasion [46]. WASF3, a Wiskott-Aldrich syndrome protein family member, has been implicated in multiple studies as a regulator of the actin cytoskeleton and in cancer invasion, which is again consistent with our results [47].…”
Section: Plos Geneticssupporting
confidence: 92%
“…Here, our RNA-seq analysis following LINC03045 KD revealed that WASF3 is a gene that was reproducibly downregulated with LINC03045 knockdown, while a correlation analysis of patient TCGA/GTEx sequencing data revealed a significant positive correlation between LINC03045 and WASF3. Additionally, the GO term for cytoskeleton organization (GO: 0007010) process was enriched for WASF3, which is consistent with prior literature that describes cytoskeletal reorganization as commonly associated with tumor invasion [46]. WASF3, a Wiskott-Aldrich syndrome protein family member, has been implicated in multiple studies as a regulator of the actin cytoskeleton and in cancer invasion, which is again consistent with our results [47].…”
Section: Plos Geneticssupporting
confidence: 92%